KAWITAN SITE AS RELIGIOUS EDUCATIONAL TOURISM IN BANYUWANGI REGENCY: SITUS KAWITAN SEBAGAI EDUWISATA RELIGI DI KABUPATEN BANYUWANGI - Ananda, Rizza; I Kadek Yudiana; Mahfud (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
The Kawitan Site in Alas Purwo, Banyuwangi Regency, has deep spiritual and historical values and great potential to be developed as a religious educational tourism destination. This study aims to analyze this potential and provide recommendations for development based on local wisdom values. The approach used is descriptive qualitative with data collection techniques in the form of in-depth interviews, participatory observation, and document studies. Informants in this study included site managers, Perhutani officers, community leaders, tour guides, and tourists. This study explores the spiritual meaning, local cultural values, and visitor motivations in interacting with the site. To analyze the data, a SWOT analysis was used to identify internal and external factors that influence site management. The IFAS and EFAS matrices were used to systematically assess strengths, weaknesses, opportunities, and threats. Furthermore, a TOWS analysis was applied to formulate an effective development strategy by utilizing the available potential and opportunities, while addressing existing challenges. The results of the study indicate that the Kawitan Site has strong religious and educational appeal, but still faces obstacles in terms of facilities, promotion, and institutional collaboration. Therefore, synergy is needed between managers, communities, and policy makers to encourage the development of religious educational tourism based on the preservation of local spiritual and cultural values.